The Impact of Inflammatory Bowel Disease Clinic On-site Vaccination Services. Issue 4 (20th September 2021) - Hussain, Nadeen; Proctor, Deborah; Al-Bawardy, Badr
Abstract: Background: Despite being susceptible to vaccine-preventable diseases, patients with inflammatory bowel disease (IBD) have low vaccination rates. The aims of this study are to examine the rates of vaccine discussion and completion among patients of an IBD clinic that offers on-site vaccinations. Methods: This is a retrospective study from March 1, 2019 to February 1, 2020 comparing vaccination discussion and completion rates for patients with IBD who visited 2 clinics—1 that offers on-site vaccination (Clinic A) and 1 that does not (Clinic B). Both clinics are staffed by the same IBD physicians and utilize an identical IBD vaccine checklist. Results: A total of 356 patients were included (64.6% Crohn's, 31.7% ulcerative colitis, 1.1% indeterminate colitis, and 2.5% pouchitis). Overall vaccine discussion rate was 77.6% in Clinic A vs 70.9% in Clinic B ( P = .15). Herpes zoster (HZ), pneumococcal, and tetanus–diphtheria–pertussis (Tdap) vaccine discussion rates were higher in Clinic A compared to Clinic B (17.8% vs 5%, P < .001, 56.3% vs 43.4%; P = .01, and 41.4% vs 21.4%, P < .001), respectively. Influenza vaccine completion and hepatitis A immunization rates were higher in Clinic A compared to Clinic B (67.8% vs 47.8%, P < .001 and 36.2% vs 22.5%, P = .005), respectively. A numerically higher percentage of patients completed the pneumococcal, HZ, and hepatitis B vaccination in Clinic A, but this difference did not reach statistical significance. Conclusions: IBD clinic on-site vaccination services enhanced vaccine discussion and completion rates. IBD clinics should offer on-site vaccination services as part of the comprehensive care of the IBD patient. Lay Summary: The rates of vaccine discussion and completion are higher for certain vaccines in the inflammatory bowel disease (IBD) clinic that offers on-site vaccination by the IBD nurse as compared with the IBD clinic that does not offer on-site vaccination services.